Social Media Construction of Political Hegemony: Analysis of the 2024 Indonesian Presidential Candidates Debate First Round - Ahmad Salman Farid; Pooja Pathak (Feedback International Journal of Communication, 2024)
This research aims to analyze the construction of social media in the context of political hegemony during the first round of the 2024 Indonesian presidential debate. Employing a social media analysis approach, this study explores how social media serves as a crucial platform in shaping and directing public opinion and how viral narratives can influence political dynamics and polarization in society. The findings reveal that social media plays a significant role as the primary platform creating a polarization of public opinion, dividing users into pro and contra groups regarding the presidential candidates. Dominant narratives are often triggered by controversial speeches or responses, sparking emotional and intense discussions among social media users. This research also highlights the importance of contextual understanding and the sustainability of facts in addressing challenges posed by distorted perceptions in the digital world. Small groups with extreme views play a crucial role in creating an echo chamber, where their perspectives are reinforced and influence wider conversations. Panelists and debate moderators also have a significant impact on shaping perceptions of presidential Candidates performances. This study provides in-depth insights into the complex dynamics of social media in the political context, opening the door to a better understanding of its influence on public opinion and social political dynamics.